Knowledge, attitudes, and practices related to COVID‐19 infection, related behavior, antibiotics usage, and resistance among Syrian population: A cross‐sectional study. Issue 6 (3rd October 2022) - Swed, Sarya; Shoib, Sheikh; Almoshantaf, Mohammad B.; Hasan, Walaa; Dean, Yomna E.; Tanas, Yousef; Bohsas, Haidara; Alibrahim, Hidar; Hasan, Mohammad M.; Ezzdean, Weaam; Ghaith, Hazem S.; Khairy, Lina T.; et al.
Abstract: Background and Aims: Antibiotic resistance is seen as a worldwide health risk as a result of the overuse of antibiotics. Many countries noted that antibiotic usage was high during the COVID‐19 pandemic. The purpose of this study is to evaluate Syrians' knowledge, attitudes, and practice about the use of antibiotics and antibiotic resistance during the COVID‐19 epidemic. Methods: A cross‐sectional study was conducted using an online questionnaire to collect the data from the Syrian population from February 5 to March 4, 2022. Syrians 18 years or older all over the world were able to participate in this study. A convenience snowball sampling method was used. SPSS version 20.0 was used to analyze the data. To examine the results, binominal logistic regression was used. Statistical significance was defined as a p  < 0.05. Results: Out of 2406 respondents, 60.2% knew that transmission of COVID‐19 could occur even if the patient has not developed any symptoms, and 91.6% were able to recognize the main clinical symptoms of COVID‐19. There was a statistically significant difference between male and female knowledge of COVID‐19 ( p  = 0.002), with males having 3.78 ± 2.1 (2.7–3.87) and females scoring 3.93 ± 2.3 (3.7–4.1). Newly graduated students have more knowledge of COVID‐19 than other subtypes of Job ( p  = 0.0001), and those with medical practice are more knowledgeable than those without ( p  = 0.0001). Only 16.6% answered that taking antibiotics would not speed up the recovery from all the infections. 65.3% answered correctly that misuse of antibiotics could cause antibiotic resistance. Conclusion: Our study concluded that the Syrian population demonstrated good knowledge of COVID‐19 and moderate acceptance of the new norm. Knowledge regarding antibiotic use and resistance and practice of preventive measures was poor, which can encourage the health authorities to develop community education programs to increase public awareness of the usage of antibiotics and safety protocols during the COVID‐19 pandemic.